2013
DOI: 10.1016/j.jnoncrysol.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness and temperature dependence of Young's modulus of a sintered albite glass

Abstract: Albite glass is an important component in many ceramic compositions, often used as liquid phase during the sintering process. Nevertheless, in spite of its almost ubiquous presence in the final microstructure of these compositions, some properties such as Young's modulus or fracture toughness have not been extensively studied in literature. This paper presents an experimental study on a sintered albite glass obtained from sodium feldspar powder. The microstructure of the resultant amorphous solid was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
8
2
Order By: Relevance
“…High‐temperature Young's modulus values for albite glass measured by Bó et al are lower than ours because they used a sintering process for synthesis that resulted in a porosity of 5% in the glass. Among all of the intermediate glasses identified in this work, albite is a unique one, whose E , B , and μ all stay nearly constant over a large temperature range as seen in Figure .…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…High‐temperature Young's modulus values for albite glass measured by Bó et al are lower than ours because they used a sintering process for synthesis that resulted in a porosity of 5% in the glass. Among all of the intermediate glasses identified in this work, albite is a unique one, whose E , B , and μ all stay nearly constant over a large temperature range as seen in Figure .…”
Section: Resultscontrasting
confidence: 71%
“…Physical properties of glasses studied in this work are shown in Table . Density of albite measured in this study was found to be slightly lower than the density of 2.382 g/cc reported by Taylor et al and higher than the value of 2.28 g/cc reported by Bó et al Refractive index of albite glass was found to match the reported value of 1.49 by Carter et al…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…Ah ump appears in the range 20-408 in the XRD patterns,w hich is presente ven for the FTO glass.T his could be attributed to theamorphous glass. [39] CoPi beingamorphous wasn ot detected by XRD. It is importantt on otet hatt races of any crystalline impurities were not detected by XRD.…”
Section: Resultsmentioning
confidence: 99%
“…52 Therefore, the absence of the interfacial cracks in the oxide pellets containing mini-pellet sintered at 1400°C or less could be attributed to the mismatch stresses reduction due to a lower initial density of the lumped Gd 2 O 3 before the insertion. The residual stress can be changed not only by changing the thermal expansion coefficient but also by changing the elastic constant, which depends on the material density.…”
Section: Fabrication Of Oxide Pellets Containing Lumped Gd 2 Omentioning
confidence: 98%